2020
DOI: 10.1002/acn3.51093
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent PJA1 variant in trigonocephaly and neurodevelopmental disorders

Abstract: Objective: Neurodevelopmental disorders (NDDs) often associate with epilepsy or craniofacial malformations. Recent large-scale DNA analyses identified hundreds of candidate genes for NDDs, but a large portion of the cases still remain unexplained. We aimed to identify novel candidate genes for NDDs. Methods: We performed exome sequencing of 95 patients with NDDs including 51 with trigonocephaly and subsequent targeted sequencing of additional 463 NDD patients, functional analyses of variant in vitro, and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The paralog ZMYND8 gene is also a transcriptional co‐repressor and histone binding protein but has selective interaction with H3.1K36me2/H4K16ac (dimethylated lysine 36 on histone 3.1/acetylated lysine 16 on histone 4), this selectivity believed to be determined in part by replacement of amino acid residues N263 and R265 51 . ZYMND8 is also associated with neurodevelopmental disorders and seizures 6,52,53 and is widely expressed in the Xenopus embryonic nervous system, overexpression inhibiting neuronal marker expression and leading to severe neural tube defects, suggesting a similar role to ZMYND11 in regulating neural differentiation 54 …”
Section: Discussionmentioning
confidence: 99%
“…The paralog ZMYND8 gene is also a transcriptional co‐repressor and histone binding protein but has selective interaction with H3.1K36me2/H4K16ac (dimethylated lysine 36 on histone 3.1/acetylated lysine 16 on histone 4), this selectivity believed to be determined in part by replacement of amino acid residues N263 and R265 51 . ZYMND8 is also associated with neurodevelopmental disorders and seizures 6,52,53 and is widely expressed in the Xenopus embryonic nervous system, overexpression inhibiting neuronal marker expression and leading to severe neural tube defects, suggesting a similar role to ZMYND11 in regulating neural differentiation 54 …”
Section: Discussionmentioning
confidence: 99%
“…16 Prior to this study, an individual with a de novo variant in ZMYND8 was reported. A small de novo ZMYND8 deletion predicted to result in a frameshift was reported by Suzuki et al 17 in an individual with trigonocephaly, speech delay and autism spectrum disorder (ASD) suggesting a role for ZMYND8 in neurodevelopmental phenotypes. In this study, we assessed clinical data from 10 unpublished individuals combined with newly ascertained information from one affected individual to firmly establish the contribution of ZMYND8 to ID.…”
Section: Introductionmentioning
confidence: 94%
“…In mice, loss of Ncb5or has been linked to insulin-deficient diabetes and other deficiencies ( Xie et al, 2004 ; Stroh et al, 2016 ; Stroh et al, 2018 ) Ncb5or contains a CS domain that is shared with other Hsp90 cochaperones, but its functional interaction with Hsp90 has not been characterized ( Benson et al, 2019 ). A mutation in CYB5R4 that leads to a truncated version of Ncb5or has been implicated in neurodevelopmental disorders ( Suzuki et al, 2020 ), but a potential mechanistic defect is unknown.…”
Section: Neurodevelopmental and Neurodegeneration Disordersmentioning
confidence: 99%